Suppression of oral cancer by induction of cell cycle arrest and apoptosis using Juniperus communis extract. Issue 9 (7th September 2020) - Lee, Ching-Chang; Hsiao, Chih-Yen; Lee, Shan-Chih; Huang, Xiao-Fan; Chang, Kai-Fu; Lee, Ming-Shih; Hsieh, Ming-Chang; Tsai, Nu-Man
Abstract: The oral cancer incidence rate is slowly increasing and is now the fifth leading cause of cancer-related death due to its high metastasis and recurrence rate. Juniperus communis is used as a traditional Chinese medicine and has been proven to have anti-cancer activity against neuroblastomas. In the present study, we further investigated the anti-cancer mechanisms of J. communis extract (JCo) on oral cancer and evaluated the synergistic effects of JCo combined with 5-fluorouracil (5-FU). We found that JCo inhibited oral cancer cell growth, and that JCo might be less cytotoxic to normal cells than to cancer cells. After JCo treatment, cell cycle arrest was observed at the G0 /G1 phase through modulation of p53/p21 and Rb signaling. JCo also caused an increase in the sub-G1 phase and cell apoptosis via the intrinsic and extrinsic apoptosis pathways. JCo combined with 5-FU presented a synergistic effect to reduce cell viability. In conclusion, JCo inhibited oral cancer cell growth by inducing cell cycle arrest and activating cell apoptosis, and JCo significantly synergized with 5-FU. JCo might have the potential to be an adjuvant and a new therapeutic drug for oral cancer treatment.